Vitamin E in the Preterm Infant: A Forgotten Cause of Hemolytic Anemia - Gomez-Pomar, Enrique; Hatfield, Emily; Garlitz, Karen; Westgate, Philip M.; Bada, Henrietta S. (American Journal of Perinatology, 2018)
Objective Vitamin E deficiency in premature infants has been associated with hemolytic anemia. Its incidence decreased after the supplementation of preterm formulas and parenteral nutrition with vitamin E. Despite this, some infants still develop hemolytic anemia and receive vitamin E.Study Design Retrospective analysis of 70 infants admitted to a level IV intensive care unit and who developed hemolytic anemia and were treated with vitamin E. Infants were classified into two groups based on whether or not they responded to vitamin E therapy. Statistical methods included the use of descriptive statistics and marginal logistic regression models.Results Low hematocrit and reticulocytosis before vitamin E administration were associated with adequate response to treatment. Thrombocytosis, iron treatment (duration and dose), gestational age, birth weight, and type of feedings were not. Infants who received a short duration of parenteral nutrition and were on oxygen responded to vitamin E therapy. Infants with a hematocrit ≤ 26% and reticulocyte of 36.1% were more likely to respond to vitamin E.Conclusion Although formulas and parenteral nutrition are supplemented with vitamin E; some preterm infants may still develop hemolytic anemia. Those with anemia, reticulocytosis, and oxygen requirement may benefit from additional vitamin E.
Keywords: vitamin E; preterm infants; hemolytic anemia; preterm anemia